Novel FBN1 gene mutation and maternal germinal mosaicism as the cause of neonatal form of Marfan syndrome. Issue 6 (25th March 2014) - Šípek, Antonín; Grodecká, Lucie; Baxová, Alice; Cibulková, Petra; Dvořáková, Magdaléna; Mazurová, Stella; Magner, Martin; Zeman, Jiří; Honzík, Tomáš; Freiberger, Tomáš
<x xml:space="preserve">Abstract</x> Marfan syndrome (MFS) is an autosomal dominant disorder caused by mutations in the fibrillin 1 gene (FBN1). Neonatal form of MFS is rare and is associated with severe phenotype and a poor prognosis. We report on a newborn girl with neonatal MFS who displayed cyanosis and dyspnea on the first day of life. The main clinical features included mitral and tricuspid valve insufficiency, aortic root dilatation, arachnodactyly, and loose skin. Despite the presence of severe and inoperable heart anomalies, the girl was quite stable on symptomatic treatment and lived up to the 7th month of age when she died due to cardiorespiratory failure. Molecular‐genetic studies revealed a novel intronic c.4211‐32_‐13del mutation in the FBN1 gene. Subsequent in vitro splicing analysis showed this mutation led to exon 35 skipping, presumably resulting in a deletion of 42 amino acids (p.Leu1405_Asp1446del). Interestingly, this mutation is localized outside the region of exons 24–32, whose mutation is responsible for the substantial majority of cases of neonatal MFS. Although the family history of MFS was negative, the subsequent molecular genetic examination documented a mosaicism of the same mutation in the maternal blood cells (10–25% of genomic DNA) and the detailed clinical examination showed unilateral lens ectopy. © 2014 Wiley Periodicals, Inc.